THE ETHANOL EXTRACT OF JUKUT PENDUL (KYLLINGA NEMORALIS) EXHIBITS INHIBITORY ACTIVITY AGAINST THE GROWTH OF STAPHYLOCOCCUS AUREUS - Niluwih, Komang Deatriasa Pakerti; Swastini, I Gusti Agung Ayu Putu; Habibah, Nur; Suyasa, Ida Bagus Oka (Meditory : The Journal of Medical Laboratory, 2023)
Staphylococcus aureus is a pathogenic bacteria that is often found to have resistance to antibiotics. Jukut pendul (Kyllinga nemoralis) extract is known to have antibacterial compounds such as flavonoids, tannins, saponins, and steroids. The purpose of this study was to determine the inhibitory ability of jukut pendul ethanol extract against Staphylococcus aureus bacteria. This research used the Kirby-Bauer disc diffusion method with five treatments within five repetitions. Data analysis was carried out using One Way Anova variance analysis. The variation in extract concentration tested was 5, 10, 20, and 40% with 96% ethanol as the control group and Ciprofloxacin as the work control. The results showed that extract concentrations of 5, 10, 20, and 40% were able to inhibit Staphylococcus aureus bacteria with an average inhibitory zone of 9,36; 10,85; 11,64; and 12.15 mm, respectively. The inhibitory zone formed indicates that jukut pendul ethanol extract has moderate to strong inhibitory ability in inhibiting the growth of Staphylococcus aureus bacteria.